Impact of sand on the water retention properties of a bentonite/sand mixture by NMR characterization - Eizaguirre Pablo; Tang Anh Minh; Maillet Benjamin; Sidi-Boulenouar Rahima; Chabot Baptiste; Bornert Michel; Pereira Jean-Michel; Dangla Patrick; Aimedieu Patrick; Talandier Jean; Vu Minh Ngoc (E3S Web of Conferences, 2023)
Blocks of compacted bentonite/sand mixture, with a 40/60 proportion in dry mass, are being studied as an elementary component in the construction of seals in the French concept for high-levelradioactive waste disposal. In the disposal, the seal will be subjected to water infiltration from the host rock. Water retention behaviour in the mixture is governed by bentonite. Nevertheless, the impact of the sand fraction, especially at high concentrations, is still unclear. The water retention curve is found experimentally for the wetting path by using vapour equilibrium technique. Moreover, NMR relaxometry tests executed atfull saturation state are presented. As a result of the comparison with experimental data reported in the past, for different mixtures -ranging from pure bentonite to 20/80 bentonite/sand mixtures-, it is concluded that all porosity in the mixture can be correctly attributed to bentonite. This conclusion simplifies mixtures to equivalent pure bentonite specimens with a dry density equal to the bentonite dry density (𝜌𝑑,𝑏) of the mixture. Moreover, an original method to compare NMR relaxation times for different bentonite/sand -or pure bentonite- mixtures is proposed. It provides the longitudinal relaxation time (T1) in saturated mixtures as a function of 𝜌𝑑,𝑏 and the montmorillonite concentration in bentonite.